2002
DOI: 10.1021/ma025541i
|View full text |Cite
|
Sign up to set email alerts
|

Bis(pseudopolyrotaxane)s Possessing Copper(II) Ions Formed by Different Polymer Chains and Bis(β-cyclodextrin)s Bridged with a 2,2‘-Bipyridine-4,4‘-Dicarboxy Tether

Abstract: Two novel nanoscale supramolecular assemblies have been synthesized from 2,2′-bipyridine-4,4′-dicarboxy-bridged bis(6-O-β-cyclodextrin)s possessing a coordinated copper(II) center threaded on different polymer chain (PPG and PDXL) respectively, and characterized by 1 H NMR, 2D NOESY, static light scattering, ESR, powder X-ray diffraction patterns, TG-DTA, STM, and TEM images, displaying two bis(pseudopolyrotaxane)s of length ca. 8-10 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…The 2,4-dinitro group is too small to block β-CD rings totally. The hypothetical structure of 19 was supported by 1 H NMR, TEM, and AFM (Figure ).
50 β-CD ladder pseudopolyrotaxane 19 : structural formula and AFM pictures. (Reprinted with permission from ref .
…”
Section: 1 Cyclodextrin Dimersmentioning
confidence: 90%
“…The 2,4-dinitro group is too small to block β-CD rings totally. The hypothetical structure of 19 was supported by 1 H NMR, TEM, and AFM (Figure ).
50 β-CD ladder pseudopolyrotaxane 19 : structural formula and AFM pictures. (Reprinted with permission from ref .
…”
Section: 1 Cyclodextrin Dimersmentioning
confidence: 90%
“…[6,9,10,24,25] The STM image of 2 ( Figure 4) [26] shows a regular arrangement of chains of supramolecules on a graphite substrate, which indicates that the polymeric rotaxanes are formed through the coordination of b-CD-DPD complexes with Ni II ions. From the size and shape of the patterns, one bright dot corresponds to a b-CD unit, which lies with its longitudinal axis parallel to the surface.…”
Section: à041 Dmmentioning
confidence: 99%
“…[7] We recently showed that the resulting complex formed from an organoseleniumbridged b-CD dimer and a platinum ion could be fabricated into bis(molecular tube)s through formation of a pesudorotaxane with poly(propylene glycol), and the bridged bis(bcyclodextrin)s and calix [4]arene derivatives could also form nanometer-sized linear aggregations by simple host-guest inclusion complexation. [8][9][10] Molecular semiconductors can also be exploited for organic electronics and single molecules can be manipulated and incorporated into nano-engineered devices at a supramolecular level by threading a chargetransport macromolecule. [11][12][13][14][15] However, higher order polymeric rotaxanes fabricated by metal-ion binding to the inclusion complexes formed between CDs and aromatic molecules have not been investigated so far.…”
mentioning
confidence: 99%
“…The supramolecular assemblies constructed by simple inclusion complexation of host CDs and guest molecules have attracted more and more attentions in recent years because of their potential to serve as molecular devices and molecular machines, as well as functional materials etc. [2][3][4][5][6] . Our recent investigations have revealed that the resulting complex of β-CDs with guest molecules is the crucial step in the formation of polymeric rotaxane [7] .…”
Section: ____________________________________________________________________________mentioning
confidence: 99%